TINJAUAN SOSIOLOGIS TERHADAP HAMBATAN PROGRAM BIMBINGAN PRA NIKAH ISLAM DI KOTA JAYAPURA - Ismail; Faisal; Muhammad Wahib; Athoillah Islamy (MIYAH : Jurnal Studi Islam, 2023)
This qualitative study in the form of nomative-empirical legal studies aims to identify the Premarital Guidance Program in Office of Religious Affairs in the Jayapura City area. Data collection was through interviews, observation, and documentation. The theory of legal effectiveness becomes the theory of analysis. Data analysis techniques use reduction, presentation, and verification. This study concludes that the obstacles to the effectiveness of the Premarital Guidance Program at the Office of Religious Affairs in the Jayapura City area are caused by various factors, among others, legal structure problems in the form of communication problems between religious extension workers and Office of Religious Affairs, and the concurrent duties of religious extension workers. Then, the problem of legal facilities in the form of budget constraints, and infrastructure for Premarital Guidance activities. Furthermore, the problem of legal culture is in the form of lack of discipline in the time of the participants of the Premarital Guidance Program. The theoretical implications of this study show that synergy of factors is needed for the effectiveness of regulatory in realizing the ideal Premarital Guidance Program.